Observed Data of Forest Fire Hotspots effects on Respiratory Disorder by Arc-GIS in Riau Province, Indonesia. Issue 1 (March 2021) - Purnomo, Eko Priyo; Rahmasari, Farindira Vesti; Trisnawati, Dina Wahyu; Agustiyara,; Erviana, Rima
Abstract: The paper shows that air quality aspects rise from forest fires in Indonesia and they have associations with a wide range of adverse health outcomes, including respiratory health problems. Due to the unpredictable nature of forest fires, it is challenging for public health authorities to evaluate the potential exposures before they occur reliably. Using GIS software, zoning was made om Riau Province, Indonesia. The data shows that the highest fire hotspot was in 2015 by 12, 854 and the lowest was 527 in 2017 as well as the lowest Respiratory Disorder Cases in 2017 was 371, 044. The Finding proves that smoke has a significant negative effect on increasing respiratory problems Therefore, it also indicates that smoke and haze forecastings are effective tools and challenging to be developed that can be used as public health predictions and establish a suitable policy on forest fires. However, their inherent uncertainties limit their widespread adoption. Observed measurements from air quality monitoring networks and remote sensing platforms are more reliable, but they are inherently retrospective.